1999
DOI: 10.1021/es9905997
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal and Spatial Variations in Human Cell Mutagenicity of Respirable Airborne Particles in the Northeastern United States

Abstract: Samples of respirable airborne particles (similar in size to PM 2.5 ) were collected at five sites in the northeastern United States every sixth day during 1995 and tested in a mutagenicity assay based on human cells. Three sites were located in Massachusetts: in downtown Boston, in a suburban area 20 km to the north, and in a rural area 100 km west of Boston. The other two sites were located in downtown Rochester in upstate New York and in a rural area 35 km to the west. Bimonthly composite samples (10-11 sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 47 publications
2
17
0
Order By: Relevance
“…32 The median value in these 15 urban areas was 1400 ng/m 3 . Studies in rural areas report values of 500 ng/m 3 in each of two eastern rural areas; 29 1900 and 3300 ng/m 3 in two Colorado towns; 33 100-400 ng/m 3 in the Smoky Mountains of Tennessee; 34 700 ng/m 3 in a Washington town; 35 200-700 ng/m 3 in six rural areas; 30 400 ng/m 3 in a rural location 150 km inland from the mid-Atlantic coast; 36 400-3300 ng/m 3 in 10 California locations; 37 and 100 ng/m 3 in the Grand Canyon. 38 The median value in these 24 rural areas was 700 ng/m 3 .…”
Section: Discussionmentioning
confidence: 99%
“…32 The median value in these 15 urban areas was 1400 ng/m 3 . Studies in rural areas report values of 500 ng/m 3 in each of two eastern rural areas; 29 1900 and 3300 ng/m 3 in two Colorado towns; 33 100-400 ng/m 3 in the Smoky Mountains of Tennessee; 34 700 ng/m 3 in a Washington town; 35 200-700 ng/m 3 in six rural areas; 30 400 ng/m 3 in a rural location 150 km inland from the mid-Atlantic coast; 36 400-3300 ng/m 3 in 10 California locations; 37 and 100 ng/m 3 in the Grand Canyon. 38 The median value in these 24 rural areas was 700 ng/m 3 .…”
Section: Discussionmentioning
confidence: 99%
“…However, Dean (28) controlled for the age at which smoking began and found that the urban-rural gradient persisted. Recent lung cancer incidence and mortality data continue to show evidence of urban-rural differences (29,30) and other studies document contemporary urban-rural gradients in the mutagenicity of airborne particulate matter across the United States (31,32). Nonetheless, the urban factor may reflect influences instead of, or in addition to, outdoor air pollution; these could include indoor air pollution, patterns of migration, occupational exposures, or factors related to population density.…”
Section: Migrant Studies and Urban-rural Comparisonsmentioning
confidence: 98%
“…NPAHs have been reported as a class of very potent mutagenic compounds [15]. In a study carried out in the NorthEastern United States, OPAHs have been reported as the most mutagenic compounds regarding human-cell mutagens in respirable airborne particles [16].…”
Section: Accepted M Manuscriptmentioning
confidence: 99%